Hydroxyglutaric Acidemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Increased urinary excretion of L-2-hydroxyglutaric acid, found in 8 mentally retarded patients from 5 unrelated families including 3 pairs of siblings seen in various centers in Europe, was reported from University Hospital Amsterdam, the Netherlands.